Mobilizing restraint : democracy and industrial conflict in postreform South Asia - Teitelbaum, Emmanuel, 1974- (Cornell paperbacks., 2011)
'Mobilizing Restraint' argues that democracies are better at managing industrial conflict than authoritarian regimes.